Discourse of the Comedy of Ubrug Sentra Agata in the Rahwana Nganjor Play - Rahayu, Zanuar Eko; Nalan, Arthur S; Dimyati, Ipit S (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2023)
This study is entitled Discourse on Comedy Serving Ubrug Sentra Agata in the play Rahwana Nganjor, which was staged during the West Java and Banten Landslide Festival in 2015. The object of the study uses the video media of performance documentation and the focus of the study is discussing discourse in comedy presentations on the play Rahwana Up. The play Rahwana Nganjor carries the theme of wayang in the Ramayana epic, the war between the Kingdom of Alengka and the Kingdom of Ayodhya is used as the setting for the event in this play. Data collection techniques were carried out through interviews, observation, and information contained in the audiovisual. Critical Discourse Analysis Van A, Dijk is used to examine the discourse in the comedy presentation by paying attention to three dimensions, including Text Dimensions, Social Cognition, and Social Context. So the data obtained that social issues in the community is used as the basis for creating comedy in Ubrug Sentra Agata.